Percutaneous repair of mitral valve regurgitation in patients with severe heart failure: comparison with optimal medical treatment. Issue 4 (4th July 2018) - Geis, Nicolas; Raake, Philip; Lewening, Markus; Mereles, Derliz; Chorianopoulos, Emmanuel; Frankenstein, Lutz; Katus, Hugo A.; Bekeredjian, Raffi; Pleger, Sven T.
Abstract: Background: Occurrence of severe mitral valve (MV) regurgitation (MR) is an independent negative predictor of mortality in patients with severe systolic heart failure (HF). This study examines clinical effects and cardiac reverse remodelling in patients with severe systolic HF receiving percutaneous mitral valve repair (PMVR) using MitraClip in comparison to patients receiving optimal medical therapy only. Methods: Between 2010 and 2014, 86 patients (Society of Thoracic Surgeons score: 10.5% ± 1.2%) with severe HF (left ventricular [LV] ejection fraction; LVEF: 25% ± 2%; LV endsystolic diameter [LVESD]: 55 ± 3 mm) and severe MR received PMVR using MitraClip. Cardiac reverse remodelling and clinical parameters were compared to HF patients with severe MR (from our HF outpatient clinic; n = 69; LVEF: 26% ± 1.4%; LVESD: 53 ± 2 mm) receiving optimal medical therapy (OMT) only. All patients received stable OMT and were characterised by echocardiography, 6-minwalk-distance test and cardiac biomarkers within a 24 months observation period. Results: PMVR in patients with end-stage HF and severe MR resulted in reduction of MR and significant additional cardiac reverse remodelling (LVEF: 26 ± 1.4 vs. 33% ± 2%, p < .05; LVESD: 53 ± 2 vs. 47 ± 2 mm, p < .05) over the 24 months observation period as compared to pharmacologically-only managed comparators. Conclusions: Both OMT and PMVR cause cardiac reverse remodelling and relief of symptoms in patients with HF and severe MR. PMVR results in significant additional cardiac reverse remodelling compared to pharmacologically-only managed patients.